2002
DOI: 10.1128/jcm.40.12.4720-4728.2002
|View full text |Cite
|
Sign up to set email alerts
|

Identification ofListeriaSpecies by Microarray-Based Assay

Abstract: We have developed a rapid microarray-based assay for the reliable detection and discrimination of six species of the Listeria genus: L. monocytogenes, L. ivanovii, L. innocua, L. welshimeri, L. seeligeri, and L. grayi. The approach used in this study involves one-tube multiplex PCR amplification of six target bacterial virulence factor genes (iap, hly, inlB, plcA, plcB, and clpE), synthesis of fluorescently labeled single-stranded DNA, and hybridization to the multiple individual oligonucleotide probes specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
118
0
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 205 publications
(122 citation statements)
references
References 41 publications
1
118
0
3
Order By: Relevance
“…During a single hybridization, arrays can integrate probes that provide microbial identification but also enclose large sets of discriminative epidemiological markers [31,31,70,182,183,198], or contain probes to detect virulence or antimicrobial resistance determinants [17,36,38,91,176]. The high parallelism of microarray systems appears particularity adapted provided their design includes the following: (1) targeted universal gene(s), (2) simplified coupling and labeling protocols, (3) exquisite sensitivity, and (4) adapted analysis strategy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During a single hybridization, arrays can integrate probes that provide microbial identification but also enclose large sets of discriminative epidemiological markers [31,31,70,182,183,198], or contain probes to detect virulence or antimicrobial resistance determinants [17,36,38,91,176]. The high parallelism of microarray systems appears particularity adapted provided their design includes the following: (1) targeted universal gene(s), (2) simplified coupling and labeling protocols, (3) exquisite sensitivity, and (4) adapted analysis strategy.…”
Section: Discussionmentioning
confidence: 99%
“…Reports have already shown that oligonucleotide microarrays can enable bacterial detection utilizing conserved bacterial genes [158], species identification [189] as well as genotyping of bacterial pathogens, by using large sets of discriminative epidemiological markers [32,36,70,183,198]. Detection of genetically encoded virulence or antimicrobial resistance determinants [17,36,112,176] may also afford a major benefit for selection of an adequate chemotherapy.…”
Section: Introduction To Microarray Technologymentioning
confidence: 99%
“…However, some authors chose genes that are more strongly related to virulence, hence considered more pathogen specific. For instance, Volokhov and colleagues [60] developed a Listeria diagnostic microarray-based on genes essential for the bacteria virulence but found in all Listeria strains, such as the invasion associated protein (iap), and in pathogenic strain-specific genes, such as hly.…”
Section: Choice Of the Target Genementioning
confidence: 99%
“…It also may allow for the detection of those mutations even when they occur at relatively low levels (up to 1%) as in the case of mixtures of quasispecies that cannot be detected by traditional direct sequencing methods (Cherkasova et al, 2003;Leberre at al., 2007). The efficiency of microarrays for identification and discrimination of closely related bacteria and viruses has been previously demonstrated Hsia et al, 2007;Laassri et al, 2003;Nordström et al, 2005;Volokhov et al, 2002;Wade et al, 2004). The use of oligonucleotide microchips for screening of random mutations is based on the ability of microarrays to identify the presence of singlenucleotide mutations in the hybridization template (Hacia et al, 1999;Urakawa et al, 2003).…”
Section: Optimization Of the Wnv Microarray Assaymentioning
confidence: 99%
“…The microarrays consisting of multiple individual short oligoprobes were shown to be an efficient and sensitive genetic method for detection of single point mutations in viral and bacterial genomes Grinev et al, 2008b;Laassri et al, 2003Laassri et al, , 2005Laassri et al, , 2007Volokhov et al, 2002). Microarray assays can also help simultaneously detect and identify the genotype and strain of common food-borne viruses without using PCR (Chen et al, 2011).…”
mentioning
confidence: 99%